2020
DOI: 10.1177/1077800420938881
|View full text |Cite
|
Sign up to set email alerts
|

They Are NotRomeo Pimps, They Are Traffickers: Overcoming the Socially Dominant Discourse to Prevent the Sex Trafficking of Youth

Abstract: Innovative research on sex trafficking is increasingly focusing on the relevance of social relationships in the process of recruitment of young women into sex trafficking. Within the dimension of social interactions, concern is growing about coercive and deceptive intimate relationship–based strategies that traffickers use to recruit young women. To research this recruitment process, the analysis and background on the Language of Desire has allowed us to identify, through qualitative methodology, the standardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 26 publications
(27 reference statements)
0
6
0
Order By: Relevance
“…At this point we can also highlight that the comments collected in Digital Magazines, FilmAffinity and interviews not only reflect a diversity of opinions and tastes in film, but the information collected can also be linked to the language of ethics and the language of desire (Flecha et al, 2013;Joanpere et al, 2021;López de Aguileta et al, 2020;Melgar Alcantud et al, 2021;Merodio et al, 2020;Rios-González et al, 2018). We found that the comments in favor of the change in James Bond and criticism of the previous model it represented -mainly present in the film reviews and interviews -are mostly made from a language of ethics.…”
Section: Discussionmentioning
confidence: 99%
“…At this point we can also highlight that the comments collected in Digital Magazines, FilmAffinity and interviews not only reflect a diversity of opinions and tastes in film, but the information collected can also be linked to the language of ethics and the language of desire (Flecha et al, 2013;Joanpere et al, 2021;López de Aguileta et al, 2020;Melgar Alcantud et al, 2021;Merodio et al, 2020;Rios-González et al, 2018). We found that the comments in favor of the change in James Bond and criticism of the previous model it represented -mainly present in the film reviews and interviews -are mostly made from a language of ethics.…”
Section: Discussionmentioning
confidence: 99%
“…Social sciences have made, and are increasingly making, contributions promoting social impact (Aiello et al, 2020 ) in education (Rios-Gonzalez et al, 2019 ; Yeste et al, 2019 ; Duque et al, 2020 ; Ruiz-Eugenio et al, 2020b ), ethnic and cultural minorities (Gómez et al, 2019 ; Khalfaoui, 2019 ; Garcia Yeste et al, 2020 ; Serradell et al, 2020 ), gender, sexuality and masculinities (Foraster and Morlà, 2019 ; Serrano Amaya and Ríos González, 2019 ; Merodio et al, 2020 ; Salceda et al, 2020 ), communication and digital media (Madrid et al, 2020 ; Pulido et al, 2020a , b ; Rodríguez et al, 2020 ) or occupation and organizations (Campos et al, 2020 ; Mara et al, 2020 ; Redondo-Sama, 2020 ; Tellado et al, 2020 ), among others. However, when we look at the scientific and theoretical production throughout the history of social sciences, a great fragmentation can be observed, having little interdisciplinarity and little connection between what authors in the different disciplines are contributing.…”
Section: The Fragmentation Of the Social Sciencesmentioning
confidence: 99%
“…However, recent studies have stressed the need to refer to these traffickers as what they are -traffickersbecause most labels emerge from the language traffickers use themselves. Additionally, the standardised use of terms such as 'loverboys' or 'Romeo pimps', together with the glamorisation of 'pimps' and trafficking, hinders the social rejection of traffickers (Merodio et al, 2020). This might be an essential preventive issue since traffickers who recruit victims through intimate ties tend to glamorise and normalise engaging in the sex trade to manipulate victims (Reid, 2014).…”
Section: Influence Of Intimate Relationshipsmentioning
confidence: 99%